Iconography of Woman Image in Sri Tanjung Relief at Candi Surowono - Giri Nugraha; I Wayan Adnyana; Wayan Karja (Institut Seni Indonesia Denpasar, 2022)
This study aims to analyze the iconographic woman image in Sri Tanjung relief at Candi Surowono located in Kediri Regency, East Java. The qualitative research done involves understanding, concepts, values, and characteristics attached to the object of research. It uses a humanities approach with Panofsky's Iconology Theory. The relief of one of the panels (1400 AD) carved at Candi Surowono is seen as an embodiment resembling two human figures. One male figure is carved holding a female figure with an expression of body anatomy full of intimacy with each other. The central human figure and the expression of holding this are present on the background of the patra motif, buds, accompanied by leaf tendrils and a motif that looks like a flower resembling a mandala is depicted shading these two human figures. The feeling of love and longing for something that cannot be described (ngalembana) is present in the embodiment of these two figures. This classic visual art presents a shock, as if space and time have melted into one. The theme of the image conveys the wisdom of the ancestors in providing a free perspective on woman, love, and compassion.